PELATIHAN PENGELOLAAN SAMPAH DALAM USAHA PENINGKATAN NILAI EKONOMI DI KAWASAN PADAT PENDUDUK, JAKARTA TIMUR - Amran, Ellyana; Nugraha, Erie Riza; Harmaini; Sumiyarti (Universitas Trisakti, 2024)
The East Jakarta area has the densest population distribution in DKI Jakarta, which causes problems in waste management due to limited housing and low public awareness regarding environmental cleanliness. This study aimed to shape community behavior and awareness regarding the importance of waste management in densely populated areas in RW 08 Temugiring, Kayu Putih. The method used is a participatory method in the form of training, discussions, and demonstrations in using recycled waste. The results of the study show that there has been a change in the behavior of respondents related to 3R knowledge, self-motivation, and the benefits of waste management actions, all of which are closely related to environmental cleanliness. The implication is that waste management requires socialization and supervision from relevant agencies, which will increase the community's active role and provide benefits both directly and indirectly related to waste management.